Towards a plan of actions for mankind : long-range mineral resources and growth v.1 : proceedings of the world conference, Paris, 9-13 September 1974 - Marois, M.; Institut de la vie. (London : New York : Pergamon., 1977)
Articles prepared for the world conference sponsored by the Institut de la vie.
Proceedings of the world conference sponsored by Institut de la vie and held in Paris, Sept. 9-13, 1974.
English or French.
At head of title: Institut de la vie.
Includes bibliographical references.
lje 24/01/2018
Loans
Keywords: Mines and mineral resources; Environmental protection; Environmental policy; Human ecology